Factors Associated With Achilles Tendon Rupture in Women's Collegiate Gymnastics. (May 2022) - Bonanno, Joseph; Cheng, Jennifer; Tilley, Dave; Abutalib, Zafir; Casey, Ellen
Background: Achilles injury risk in women's collegiate gymnastics is 10-fold higher than in all other collegiate sports. This study aims to identify risk factors for Achilles tendon ruptures in collegiate female gymnasts. Hypothesis: Gymnasts with Achilles tendon ruptures will be more likely to report early gymnastics specialization, elite-level training before college, and performance of high-difficulty skills on floor and vault. Study Design: Cross-sectional study. Level of Evidence: Level 4. Methods: Anonymous surveys were distributed to current and former collegiate female gymnasts, aged 18 to 30 years, via coaches, athletic trainers, Twitter, and ResearchMatch. Information about Achilles tendon ruptures, gymnastics-related injuries, sport specialization, event/skills participation, and medication use were collected. Results: A total of 581 gymnasts were included. One hundred gymnasts (17.2%; 95% CI: 14.1%-20.3%) reported Achilles tendon ruptures during collegiate training or competition. Most ruptures (91%) occurred on floor exercise; 85.7% of these occurred during back tumbling-take-off. Compared with gymnasts without ruptures during college, a greater percentage of gymnasts with ruptures competed at a Division I program, trained elite, competed difficult vaults and floor passes before and during college, competed in all 4 events during college, identified as Black/African American, and used retinoid medications. Conclusion: Achilles tendon ruptures are more common in women's collegiate gymnastics than other sports. Competing at the elite level, performing difficult floor and vault skills, and competing in all 4 events may increase the risk for an Achilles tendon rupture. Potential nontraining risk factors include retinoid exposure and Black/African American race. Future studies regarding the mechanisms of Achilles tendon ruptures in female collegiate gymnasts are warranted. Clinical Relevance: Collegiate gymnasts who compete at the elite level, perform high levels of difficulty on floor and vault, and compete in all 4 events may be at increased risk for Achilles tendon ruptures.